Burst-Suppression Ratio on Electrocorticography Depends on Interelectrode Distance. Issue 2 (April 2016) - Moldovan, Mihai; Calin, Alexandru; Kumaraswamy, Vishakhadatta M.; Braver, Diana; Simon, Mirela V.
Abstract : Introduction: With deepening of anesthesia-induced comatose states, the EEG becomes fragmented by increasing periods of suppression. When measured from conventional EEG recordings, the binary burst-suppression signal (BS) appears similar across the scalp. As such, the BS ratio (BSR), quantifying the fraction of time spent in suppression, is clinically considered a global index of brain function in sedation monitoring. Recent studies indicate that BS may be considerably asynchronous when measured with higher spatial resolution such as on electrocorticography. The authors investigated the magnitude of BSR changes with cortical recording interelectrode distance. Methods: The authors selected fronto-parietal electrocorticography recordings showing propofol-induced BS recorded via 8-electrode strips (1-cm interelectrode distance) during cortical motor mapping in 31 patients. For 1-minute epochs, bipolar recordings were computed between each electrode pair. The median BSR, burst duration (BD), and bursting frequency were derived for each interelectrode distance. Results: At 1-cm interelectrode distance, with increasing BSR, BD decreased exponentially. For a BSR between 50% and 80%, BD reached a plateau of 2.1 seconds while the bursting frequency decreased from 14 to 6 bursts per minute. With increasing interelectrode distance, BD increased at a rate of 0.2 seconds per cm. This correlated with a decrease in BSR with distance that reached the rate of −4.4 percentage per centimeters during deepest anesthesia. Conclusions: With increasing cortical interelectrode recording distance, burst summation leads to an increasing BD associated with a reduction in BSR. Standardization of interelectrode distance is important for cortical BSR measurements.